Enhancing the Sequential Conversion‐Alloying Reaction of Mixed Sn–S Hybrid Anode for Efficient Sodium Storage by a Carbon Healed Graphene Oxide. Issue 4 (24th November 2017) - Kim, Joo‐Hyung; Jung, Young Hwa; Yun, Jong Hyuk; Ragupathy, P.; Kim, Do Kyung
Abstract: To date, the possible depletion of lithium resources has become relevant, giving rise to the interest in Na‐ion batteries (NIBs) as promising alternatives to Li‐ion batteries. While extensive investigations have examined various transition metal oxides and chalcogenides as anode materials for NIBs, few of these have been able to utilize their high specific capacity in sodium‐based systems because of their irreversibility in a charge/discharge process. Here, the mixed Sn–S nanocomposites uniformly distributed on reduced graphene oxide are prepared via a facile hydrothermal synthesis and a unique carbothermal reduction process, producing ultrafine nanoparticle with the size of 2 nm. These nanocomposites are experimentally confirmed to overcome the intrinsic drawbacks of tin sulfides such as large volume change and sluggish diffusion kinetics, demonstrating an outstanding electrochemical performance: an excellent specific capacity of 1230 mAh g −1, and an impressive rate capability (445 mAh g −1 at 5000 mA g −1 ). The electrochemical behavior of a sequential conversion‐alloying reaction for the anode materials is investigated, revealing both the structural transition and the chemical state in the discharge/charge process. Comprehension of the reaction mechanism for the mixed Sn–S/rGO hybrid nanocomposites makes it a promising electrode material and provides a new approach for the Na‐ion battery anodes. Abstract : The specially designed mixed Sn–S/carbon‐healed graphene oxide (GO) hybrid anode offers adequate space to accommodate large amount of sodium ions, overcoming intrinsic nature of tin sulfide. The ultrafine nanoparticles of SnS with 2 nm on GO ensure the maximum specific capacity of 1230 mAh g −1 at a current density of 25 mA g −1, revealing the significant enhancement of the sequential conversion‐alloying reaction.